HYDROCEPHALIC FETUS WITH WRY NOSE AND ITS MANAGEMENT THROUGH FETOTOMY IN A MARE - SUTARIA, TV; NAKHASHI, HC; SUTARIA, PT; CHAUHAN, PM; RAVAL, SH; SUTHAR, BN (The Indian Journal of Animal Reproduction, 2016)
A case of dystocia in mare due to hydrocephalus fetus was successfully managed by partial fetotomy. The yolk sac remnant was found attached to the placenta. Histopathology of brain tissue revealed wide perivascular spaces and decreased cellularity in granular cell layer with interstitial edema.
Keywords: Fetotomy; Histopathology; Hydrocephalus; Mare; Yolk sac remnant